Penguatan Ekonomi Lokal Melalui Pengolahan Serat Nanas Menjadi Produk Fashion Accessory - Robbani, Jaisyur; Kamal, Moh. Zainol; Aisyah, Siti; Yamin, Ashabul (Lembaga Penerbitan dan Publikasi Ilmiah, 2024)
Abstract The potential of Ellak Laok Village in the agricultural aspect, especially Pineapple fiber, has its own potential. This is because the materials used for this craft are very easy to obtain, farmers can harvest the pineapple fiber material on every roadside in Ellak Laok village. The abundance of pineapple fiber plants in Ellak Laok village is one of the reasons for this Community Service objective. The only craft product produced by pineapple fiber craftsmen in Ellak Laok village is tie rope or slap rope. The problems faced by pineapple fiber farmers in Ellak Laok village are limited tools and lack of knowledge and skills in processing pineapple fiber. Another problem faced is that the amount of pineapple fiber is abundant, while market demand is low, so the pineapple fiber will not sell, as a result the pineapple fiber becomes damaged or torn and if it is damaged it cannot be reprocessed. This will cause losses for farmers. So, pineapple fiber farmers need to get attention to change their mindset to not only be able to farm, but also be able to process agricultural products. The method implemented in this community service lecture is to provide guidance and training from production aspects and business management aspects. The results of this Community Service are providing training on processing pineapple fiber into bags and other creative products that can improve the community's economy. Keywords: community engagement; farmers; fashion; micro-economics empowerment; nature; villages Abstrak Potensi Desa Ellak Laok dalam aspek pertanian khususnya serat nanas menjadi potensi tersendiri. Pasalnya bahan yang digunakan kerajinan tersebut sangat mudah untuk didapatkan dan para petani dapat memanen bahan tersebut karena nanas tumbuh hampir di setiap pinggiran jalan yang berada di Desa Ellak Laok. Melimpahnya tumbuhan serat nanas di Desa Ellak laok menjadi salah satu alasan tujuan pengabdian kepada masyarakat ini. Satu-satunya produk kerajinan yang dihasilkan oleh pengrajin serat nanas di Desa Ellak Laok yaitu tali ikat atau tali tampar. Permasalahan yang dihadapi oleh petani serat nanas di Desa Ellak Laok adalah keterbatasan alat yang dimiliki, kurangnya pemahaman tentang produk-produk kreatif berbahan dasar serat nanas, dan keterampilan dalam mengolah serat nanas. Permasalahan lain yang dihadapi yaitu jumlah serat nanas yang melimpah, sementara permintaan pasar rendah yang membuat serat nanas tidak laku dijual mentah. Akibatnya, serat nanas menjadi rusak atau koyak. Apabila telah rusak serat nanas sudah tidak dapat diolah kembali. Hal ini akan menyebabkan kerugian bagi sejumlah petani nanas. Pengabdian kepada masyarakat ini bertujuan untuk meningkatkan gerakan ekonomi mikro bagi petani nanas di kawasan Desa Ellak Laok. Sebagai fasilitator, para tim pengabdian kepada masyarakat telah banyak mendapatkan kontribusi positif dan antusiasme yang tinggi dari para petani nanas. Kata kunci: alam; pemberdayaan ekonomi mikro; pengabdian kepada masyarakat; petani; desa